2013
DOI: 10.1088/0953-8984/25/8/086001
|View full text |Cite
|
Sign up to set email alerts
|

An integrated study of thermal treatment effects on the microstructure and magnetic properties of Zn–ferrite nanoparticles

Abstract: The evolution of the magnetic state, crystal structure and microstructure parameters of nanocrystalline zinc-ferrite, tuned by thermal annealing of ∼4 nm nanoparticles, was systematically studied by complementary characterization methods. Structural analysis of neutron and synchrotron x-ray radiation data revealed a mixed cation distribution in the nanoparticle samples, with the degree of inversion systematically decreasing from 0.25 in an as-prepared nanocrystalline sample to a non-inverted spinel structure w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 59 publications
0
26
0
1
Order By: Relevance
“…For Fe 3 O 4 (structural analog of Ni 1‐x Zn x Fe 2 O 4 ferrites), for example, neutron, X‐ray diffraction studies, electron microscopy, and nuclear magnetic resonance, it was shown that the structure of the low‐temperature phase has the form of monoclinic supercell with symmetry group Cc. Similar examples can be cited …”
Section: Sample Preparationmentioning
confidence: 67%
See 2 more Smart Citations
“…For Fe 3 O 4 (structural analog of Ni 1‐x Zn x Fe 2 O 4 ferrites), for example, neutron, X‐ray diffraction studies, electron microscopy, and nuclear magnetic resonance, it was shown that the structure of the low‐temperature phase has the form of monoclinic supercell with symmetry group Cc. Similar examples can be cited …”
Section: Sample Preparationmentioning
confidence: 67%
“…The latter brings about the variation of exchange spin oscillations in them that is experimentally confirmed by EPR investigations given in papers . We notice that the presence of lines referred to magnon oscillations is not good interpreted with two‐sublattice model of Ni 1‐x Zn x Fe 2 O 4 ferrites, magnetic space group of which published, for example, in Litvin and does not take in account the weak magnetic field of jumping 3d‐electrons . In order to explain them, it is more reasonable to use the model to take into account the magnetic ordering related to the presence of jumping 3d‐electrons, which forms the third weak magnetic sublattice.…”
Section: Raman Spectra Of Ni1‐xznxfe2o4 Ferritesmentioning
confidence: 80%
See 1 more Smart Citation
“…The conductivity and Neel temperature dependence with grain size has been investigated in nanocrystalline cobalt ferrite powder for one composition only, namely CoFe 2 O 4 [19][20][23][24]. Most of the magnetic or electric investigations of nanoparticles of cobalt ferrites in literature concern Cd , Al or Zn doped ferrites [25][26][27]. Magnetic properties and transport mechanisms of cobalt ferrites Co x Fe 3-x O 4 with various compositions were studied [28], but in that case the grain sizes were in the micronic range.…”
mentioning
confidence: 99%
“…Values of QS of QS D1 = 0 33 mm/s and QS D2 = 0 40 mm/s obtained at 800 C are in agreement with the values observed for bulk sample. 8 At 300 K the magnetization M(H) curve for Zn0 and Zn300 shows nearly zero coercivity, 4 in agreement with the superparamagnetic behavior expected for these nanoparticles on the time scale of the magnetization measurement time M ∼ 100 s. Whereas for a typical dc magnetization measurement the M is ∼ 10 2 s, for Mössbauer spectroscopy the measuring time depends on the Larmor precession time L of the nuclear magnetic moments, with L = 10 −8 -10 −9 s in the case of 57 Fe nuclei. Accordingly, room temperature Mössbauer spectra for Zn0 show magnetic order.…”
Section: Introductionmentioning
confidence: 99%